ТОК НЕБАЛАНСА И ТОК ПУЛЬСАЦИЙ ПРИ НЕСИММЕТРИЧНОМ НАПРЯЖЕНИИ - Сиротин, Ю.А. (Інститут електродинаміки НАН України, Київ, 2012)
For three-phase system with an asymmetric sinusoidal voltage at the point of connection asymmetrical loading two orthogonal decomposition of full three-phase current are considered. The first expansion is associated with the expansion of the current along the voltage vector and provides two components: the balanced current and the unbalanced current. The second expansion is associated with the expansion of the current along the (complex) conjugate of the voltage vector and gives the two components: the pulsating current and the non-pulsating current. Two power equations are obtained. It is shown how these expansions are related to each other. The results of numeric modeling are given. References 7.